Thyroid Nodules of Iraqi Patients with Acromegaly - Nihad Abdallah Selman1, Abbas Mahdi Rahma2, Atheer Yass Ali3, Hayder K. Abed4 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Acromegaly is a chronic endocrine disorder caused by excessive secretion of growth hormone. The incidence of malignancy like colorectal carcinoma is well documented to increase in patients with acromegaly. While the real incidence of thyroid neoplasm in these patients are not well known.Aims: Find out the rate of structural thyroid disorders in a sample of Iraqi patients with acromegaly; Identify the rate of thyroid malignant transformation in patients with acromegaly.Settings and Design: A case control studyMethods and Material: seventy patients with acromegaly were enrolled compared with 70 controls from 2 endocrinology centers from Jan. -Dec. 2017. Their mean age 46+/-11years ;41(58.5%) males. Thyroid ultrasound was conducted for all participants while fine needle aspirate conducted for those with nodule diameter ?1cm.Results: . Goiter was founded more in patients with acromegaly versus control group (81.4% vs 18.5% respectively ;P<0.0001) .The overall nodular thyroid disease were found in (61.4%) acromegalic patients(of those : (11.4%) had single thyroid nodule and (50%) had multiple thyroid nodules. The ultrasonic feature of thyroid nodule were suspicious in (13.9%) of acromegaly group and none in control; P<0.0001). The fine needle aspirate results were suspicious in(9.3%) acromegaly group versus none in control group, P<0.05). One patient (2.3%) with acromegaly had papillary thyroid carcinoma and none in control; P=0.31).Conclusions: Nodular thyroid disease were more prevalent in Iraqi patients with acromegaly but the risk of malignancy is not significantly different from normal population.